PROSPECTS FOR IMPROVING THE DEVELOPMENT OF TEACHING MATHEMATICS IN THE CONTEXT OF THE NATIONAL CURRICULUM OF UZBEKISTAN - Djumayev Mamanazar Irgashevich (Uzbekistan Open Conference, 2025)
The article considers the issues of the concept of prospects for improving the development of teaching mathematics in the context of the national curriculum of Uzbekistan. In the national curriculum for quality education criteria, at the same time, there are subjects - mathematics, physics, chemistry, where so-called text problems are solved. Solving text problems in these subjects is considered as a subject of special study.
Keywords: mathematics; geometry; problem solving; national curriculum; education; formation; training